The mirative and scalar meaning of even - Olivier Simonin (Anglophonia, 2018)
The analysis I develop here draws on the concept of mirativity (DeLancey 1987) and on Kay’s (1990) insight into the scalar nature of even. I show that even calls for the reconstruction of an implicit scale, on which the element highlighted by this adverbial marker stands out as the most (or more) surprising in the set considered. This non-referential, non-propositional meaning of even is likely to trigger a series of inferences, whose status is duly discussed, and to strengthen or weaken other derived assumptions, and even to guide their derivation itself.